Fiscal Performance, Institutional Design and Decentralization in European Union Countries - Eyraud, Luc (IMF Working Papers; Working Paper, 2012)
This paper analyzes the impact of decentralization on overall fiscal performance in the European Union, taking into account fiscal institutional arrangements. We find that spending decentralization has been associated with sizably better fiscal performance, especially when transfer dependency of subnational governments is low. However, subnational fiscal rules do not seem to be associated with better performance.